Correction: Real-space evidence of the equilibrium ordered bicontinuous double diamond structure of a diblock copolymer. Issue 20 (5th May 2015) - Chu, C. Y.; Jiang, X.; Jinnai, H.; Pei, R. Y.; Lin, W. F.; Tsai, J. C.; Chen, H. L.
Abstract : Correction for 'Real-space evidence of the equilibrium ordered bicontinuous double diamond structure of a diblock copolymer' by C. Y. Chu et al., Soft Matter, 2015, 11, 1871–1876.